Göteborgs Konstmuseum : Malerisamlingen 1979. (Göteborg : Göteborgs Konstmuseum, 1979)
Abrahamson, Florence ; Acke, Johan Axel Gustaf ; Adriaenssen, Alexander ; Adrian-Nilsson, Gösta ; Adzak, Roy ; van Aelst, Willem ; Agger, Knud ; Aguéli, Ivan ; Ahlgrensson, Björn ; Ahnoff, Tore ; Alfelt, Else ; Almqvist, Ester ; Amelin, Albin ; Ancher, Anna ; Ancher, Helga ; Ancher, Michael ; Andersson, Allan ; Andersson, Gustaf ; etc.
Zweeds & Engels
boek